Module-Inverters (Microinverters): Influence of Module Size on Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EU PVSEC 2021))
Efficiencies and energy yields of microinverters available on the market during 2014‒2021 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp (until 2020) and 360 Wp (starting 2021). Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each microinverter have been recorded by individual calibrated electricity meters. CEC and EU efficiency rankings have been computed and compared. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation y = ax + b resulting in the actual yield, any module & inverter configuration can be characterized by just the coefficients a and b.
Keywords: AC-modules; Microinverter; Power Conditioning; Efficiency; Yield; PV module size; saturation; performance